Microorganism and Physiochemical Characteristic of High-salt (Suan Yu), a Traditional Chinese Fermented Fish. Issue 8 (14th September 2021) - Lin, Chengxing; Zhang, Furong; Yang, Qin; Meng, Ju; He, Laping; Deng, Li; Ye, Chun; Zeng, Xuefeng
ABSTRACT: Microorganisms and physiochemical characteristics were determined in traditional high-salt fermented fish products from six different regions. Results indicated that Lactobacillus content was 7.14–7.65 log CFU/g, and yeast content was 6.21–6.54 log CFU/g in the high-salt fermented fish samples. Enterobacterium content was below the detectable limit, and the dominant Lactobacillus species was Lactobacillus plantarum . The pH value was 4.14–4.73, and the protein content reached 19.37–28.38%. The sodium dodecyl sulfate-polyacrylamide gel electrophoresis results showed that myofibrillar proteins in fish were obviously degraded. Trichloroacetic acid-soluble peptide content was 901–1061 mg/tyrosine kg, and the fat and NaCl contents were 0.92–4.79% and 5.59–7.44%, respectively. Free amino acids and free fatty acids were 1332–2380 mg/100 g and 8.95–23.4 mg/fat g, respectively. The content of thiobarbituric acid reactive substances was 1.97–4.26 mg/kg, the total volatile basic nitrogen was 12.7 ~ 38.9 mg/100 g, and the content of biogenic amine was 26.3–34.6 mg/kg.